Missing the starting gun? Entry timing decisions into new market niches - Marco S. Giarratana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
This study analyzes incumbent entry timing decisions in new markets in the case of Encryption Software (ES). In ES first technological movers were slow to enter the downstream market, losing their initial advantages to the benefit of newcomers. This work tests the hypothesis that this wait-and-see strategy was an optimal choice compared to the assumption of inertia embedded in the decision process of potential entrants. We find that entry decision is not the outcome of firm rational balancing among different strategic variables, but it is more similar to a heuristic process that fails to accommodate the full logic of decision.
Keywords: 330; Entry; Entrepreneurship; Innovation; Software; Markteintritt; Terminplanung; Nischenstrategie; Software; Welt